Low-carbon supply chain model under a vendor-managed inventory partnership and carbon cap-and-trade policy - Ririn Diar Astanti; Yosef Daryanto; Parama Kartika Dewa (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Nowadays, companies are collaborating and forming supply chain partnerships under a certain scheme, such as a vendor-managed inventory scheme. The collaboration increases the supply chain's visibility, which leads to cost efficiency. It may also contribute to enhancing the supply chain's green performance. This paper presents a supply chain inventory model to guide managers in making optimal inventory decisions considering the logistics cost and carbon emissions. A vendor supplies products under a vendor-managed inventory; hence, it is responsible for the logistics activities. The effect of product deterioration and quality problems are also considered, in which the vendor performs a 100% quality inspection. A carbon price is imposed on total emissions from production and logistics activities under a cap-and-trade regulation. The result is inventory decisions regarding the optimal delivery quantity as well as the delivery frequencies that minimize the total costs. The reduction in total carbon emissions from the decisions was also studied.
Keywords: 650; cap-and-trade; carbon emission; deterioration; imperfect quality; vendor-managed inventory